Estimation of the thermal structure of a young orogenic belt according to a model of whole-crust thickening - Teh-Ru Alex Song; Kuo-Fong Ma (My University, 2002)
A comprehensive understanding of the thermal properties beneath the Central Range of Taiwan is essential to decipher the process of mountain building and inter- pret the observed geophysical features, such as seismic velocity and seismicity. A ﬁrst- order-approximation thermal model based on crustal thickening followed by constant erosion processes is described for the Central Range. The effect of groundwater cir- culation on the observed surface heat ﬂow has been excluded in our evaluation. Our results indicate that crustal thickening causes a decrease in the geothermal gradient and the temperature. Erosion causes an increase in the geothermal gradient and the temperature. Throughmodeling, we derived the optimumgeothermbelow theCentral Range by considering a thickening factor of 2 for crustal thickening occurring at 10 Ma following constant erosion since 5 Ma. The preferred ﬁnal geotherm estimated a moderate geothermal gradient of ~17°C/km and a temperature of ~210–550°Cat a depth of 10–30 km. The uncertainties in the thickening factor, the time of crustal thickening, and the prethickening crustal thickness have a temperature-difference effect of only a few tens of degrees compared to the temperature yielded by the pre- ferred ﬁnal geotherm. Other geotherm parameters such as radiogenic heat ﬂow, scale depth, and surface heat production are also tested in the ﬁnal geotherm calculations. Seismicity cutoff depth (i.e., the brittle-to-ductile transition depth) and seismic Qp values set limits on the middle- and lower-crust temperatures determined by our model. The resulting moderate geothermal gradient differs from the notion that the crust beneath the Central Range is “hot,” although the temperature in the shallow crust needs further investigation.